Identification of damages to building structures due to roots of trees - Halwatura, R.U.; Jayawardena, V.G.N.P.; Somarathna, H.M.C.C. (My University, 2012)
When trees are planted too close to a building, the roots of them are causing damages to that building in both direct and indirect ways. In many cases, these subterranean problems go unnoticed, until cracks appear on surfaces. The remedial works for such cases can be always difficult and expensive. This research was carried out to identify the causes and effects of not using the safe planting distances and then it is extended with a detail survey to find safe distances using 5 categories of trees, which are most common in Sri Lanka. It was noted that the direct damages to civil structures are very common here in Sri Lanka. It was observed that the damage from Bodhi tree is much greater than other trees. Therefore, its’ safe planting distance is around 11 metres. Safe planting distances for Tamarind and Royal Poinciana are in a range between 6 to 7 metres. For Jack & Mango tree, it is about 4 to 5 metres. So these safe planting distances has presented numerically in this report.
Keywords: Subterranean problems; Remedial works; Safe distances; Direct and Indirect damages